Platycodi Radix Beverage Reduced the Postprandial Lipemia Response to a High-fat Load in Randomized Controlled Trials of Healthy Subjects (P12-009-19). (13th June 2019) - Lee, Inhye; Lee, Hansol; Kang, Seunghee; Park, Soo-yeon; Lim, Yeni; Kwon, Oran
Abstract: Objectives: High postprandial lipemia is a characteristic of metabolic abnormality recognized as a risk factor inducing cardiovascular disease. The objective of this study was to investigate the effects of Platycodi radix (PR) beverage on postprandial lipemia response after challenging with a high-fat/sugar load using both single-dose cross-over and 8-week repeated paralleled designs in healthy subjects. Methods: A total of 52 and 96 subjects were included in the two studies, respectively. Postprandial blood samples were collected at designated time points from 0 to 6 hours after a high-fat load at each visit to determine triglyceride (TG) and lipoprotein lipase (LPL) activity and mass in plasma, chylomicron and very low-density lipoprotein (VLDL). A general linear mixed-effect model analysis of time point values and area under the curves (AUCs) was performed to estimate the effect of PR beverage on postprandial lipemia response. Results: In a single-dose cross-over design study, PR beverage consumption significantly increased lipoprotein lipase mass ( P = 0.011, β estimate = 4.295) and reduced TG concentration in VLDL ( P = 0.038, β estimate = −52.69) at 6-hour as compared to those in placebo consumption with a high-fat load. Postprandial TG responses as measured by AUC for 6 hours were significantly correlated with a high-fat dietary score MEDFICTS in chylomicron ( r = 0.276, P = 0.008) and VLDL ( r = 0.213, P = 0.040). In a 8-week repeated parallel design study, postprandial lipemia responses were compared considering the interaction between group and week. PR beverage consumption decreased postprandial serum TG response (AUCn, P = 0.039; total AUC, P = 0.088). In addition, PR increased plasma LPL mass (AUCn, P = 0.076) that is a clearing factor that hydrolyzed TG of chylomicron and VLDL in the lipoprotein metabolism. Conclusions: In both of single and long-term intake, PR beverage consumption improved the degradation of postprandial TG level with increasing postprandial LPL mass. However, detail LPL mechanisms of PR consumption should be further analyzed. Funding Sources: This work was carried out with the support of "Cooperative Research Program for Agriculture Science & Technology Development" Rural Development Administration, Republic of Korea and the BK21 PLUS program of the Ministry of Education.